Implementing public policy An introduction to the study of operational governance - Hill, Michael Hupe, Peter (Sage, 2002)
This second edition of Hill and Hupe's popular textbook introduces students to the major themes in the study of public policy implementation and relates them to contemporary developments in thinking about governance. Fuly revised and updated, the book stresses the continuing importance of a focus on the implementation part of policy processes. Hill and Hupe suggest strategies for future research on the implementation and identify modes of managing implementation as operational governance Designed for an international audience, this is a core text for upper-level undergraduate and graduate students studying or conducting research in public policy, social plicy, public management, public administration and governance.